Mies - Mertins, Detlef, 1954-2011 (London : Phaidon, 2014)
Ludwig Mies van der Rohe is one of the twentieth century's most influential architects. His most well-known projects include the Barcelona Pavilion in Spain (1929); the Seagram Building in New York (1954-56); the Farnsworth House (1945-50), 860 and 880 Lakeshore Drive (1945-51) and the IIT Campus (1939-58), all in and around Chicago, and the New National Gallery in Berlin (1962-68). These are only a few of Mies's pavilions, houses, skyscrapers and campuses, which all epitomized a radically new structural and spatial clarity. The purity of his Mies's architecture is almost surprising in light the diversity of his interests. An auto-didact, Mies studied philosophy and science as well as design. Author Detlef Mertins, spent over ten years researching and writing this comprehensive monograph. In addition to traveling to see the buildings and reading nearly everything written by and about Mies, Mertins also conducted a detailed study of the architectural, philosophical and scientific literature in Mies's own library. The result is a lucid text that not only gives the reader detailed insight into all of Mies's work, but which also explores the variety of ideas that influenced this exceptional figure. The scholarship is rigorous, but the accessible writing and the highly visual, project-by-project presentation also invites those readers who possess an interest in the topic, but who lack detailed knowledge in it. Arranged in chronological order, the book's five sections and its conclusion offer a synthetic portrait of Mies's career and reception, spanning sixty years, two continents and two world wars.
Keywords: Mies van der Rohe, Ludwig, -- 1886-1969.; Architects -- 20th century -- Germany; Architects -- 20th century -- United States; Architecture, Modern -- 20th century